2019
DOI: 10.3390/ma12050792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on the Compressive Behavior of Zinc Alloy ZA27 Syntactic Foam

Abstract: Zinc alloy (ZA27) syntactic foams (SF) were manufactured using expanded perlite (EP) particles and counter-gravity infiltration casting. Due to a variation of the metallic matrix content, the density of the produced foam samples varied from 1.78 to 2.03 g·cm−3. As-cast and solution heat-treated samples were tested to investigate the compressive properties of the ZA27 syntactic foam. To this end, quasi-static compression tests were conducted. In addition, microstructural analysis of the as-cast and heat-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…This is of particular interest for materials showing brittle deformation and shear failure. It has been previously shown that T6 thermal treatment increases the ductility of the matrix alloy and the MSFs [29], which favours layer-by-layer deformation. At higher strains ε > 0.3, the deformation transitions to the non-compacted FG-MSF layers.…”
Section: Mechanical Propertiesmentioning
confidence: 95%
“…This is of particular interest for materials showing brittle deformation and shear failure. It has been previously shown that T6 thermal treatment increases the ductility of the matrix alloy and the MSFs [29], which favours layer-by-layer deformation. At higher strains ε > 0.3, the deformation transitions to the non-compacted FG-MSF layers.…”
Section: Mechanical Propertiesmentioning
confidence: 95%
“…Typically, in these materials, the size, or at least the size distributions, of hollow fillers are deliberately set, while their relative position can range from arbitrary to ordered. Among them, metal matrix syntactic foams (MMSFs) are high-density foams produced with a metallic (Al [2][3][4][5], Mg [6][7][8][9], Zn [2,[10][11][12], Ti [13][14][15], or Fe [16][17][18][19][20] based) matrix and various types of porous fillers (hollow spheres [21] or other porous particles [22]) by molten metal infiltration [23,24]. MMSFs can be utilized as high-performance energy absorbers in vehicles [25] and defensive technologies [26], or as lightweight structural elements.…”
Section: Introductionmentioning
confidence: 99%
“…Since the original aim of the production of MMSFs was to provide low-weight structural materials with high energy absorbing capacity, the matrix materials of MMSFs are often come from the lightweight alloys such as aluminium (most often, [1][2][3][4][5][6][7][8][9][10][11][12]) and magnesium [13][14][15][16]. However, efforts have been invested into the production of different MMSFs with iron- [17][18][19], titanium- [20][21][22] or zinc [23][24][25][26][27][28] alloys. Regarding the filler of MMSFs the first studies have been done on fly-ash cenospheres [29][30][31][32] as hollow mixed oxide, porous and cheap by-product of thermal power plants, with large scatter in the properties of the individual particles.…”
Section: Introductionmentioning
confidence: 99%